Infográfico animado sobre o plano de parto como diretiva antecipada de vontade: proposição tecnológica - Santos, Aline Ost dos (2023)
INTRODUCTION: Birth Plan is an anticipated record of a woman's wishes about the care and procedures she accepts or refuses to undergo during childbirth, constituting a kind of Advance Directive of Will. OBJECTIVE: To build a technological proposition of an animated infographic about the Birth Plan as an Advance Directive of Will for the use of pregnant women. METHOD: Methodological study with production of technological proposition with interface in three steps of the ADDIE model. This model consists of Analysis (A), Design (D), Development (D), Implementation (I) and Evalaution (E). The context analysis (A), which subsidized the construction of the content of the technological proposition roadmap, was carried out through narrative and integrative reviews, selection of official documents from the World Health Organization and the Ministry of Health, and field research. The qualitative data collection occurred through semi-structured interviews with ten puerperae assisted in Primary Health Care in a municipality of the Western Border of the State of Rio Grande do Sul conducted from October 2021 to March 2022 with an average duration of 33 minutes. The data from the field research were submitted to textual discourse analysis. In the Design stage (D) the project, the script, the art direction, the voice recording, the storyboard, and the animatic were built. The D and D stages were carried out with the assistance of a professional and an undergraduate student of industrial design from October 2021 to November 2022. The Development (D) contemplated the production of the animated infographic with the union of the animatic and the voice recording in an animated form and condensed into a video. The study obtained approval from the Research Ethics Committee of the institution under opinion CAAE 52384521.8.0000.5346. Results: The construction of the technological proposition of an animated infographic about the birth plan as an advance directive of will culminate in a video with 13 minutes and 26 seconds. The animated infographic addresses the construction of the birth plan and how health professionals can support this development with information about obstetric practices for clinically led and shared decision making. Knowledge of recommended and not recommended practices for a positive prenatal, intrapartum, and childbirth experience. It is understood that making wishes explicit could have potential bias regarding recorded decisions. The decision is the woman's with encouragement of the partner's participation in the care of the mother-baby binomial. These decisions are registered, but are not visible in the infographic, since one must take into consideration the singularity of the woman and baby's clinical condition as well as their wishes and desires. FINAL CONSIDERATIONS: The animated infographic is a technological proposition with the potential to enable women to learn about the concept of birth plan as an advance directive of will for a positive birth experience.